THE IMAGE OF RELIGIOUS VIEWS IN THE “BOBURNOMA” - Sayipova, Dilafruz (FILOLOGIYA UFQLARI JURNALI, 2022)
This article examines the issue of the direct influence of the Naqshbandi sect and its representatives in the social and political life of Zahiriddin Muhammad Babur, in public administration and, most importantly, in his personal life, in the formation of faith. The role of this sect in the formation of the qualities of compassion, forgiveness, generosity, courage, and the strength of faith, which are characteristic of Babur’s character, has also been studied. It is based on the fact that this doctrine, which he believed in the victory of Babur in battles, and sometimes in the absolute spiritual victory over pride and lust, and the support of his great leaders, was immense. The material and spiritual education that Bobur received from his teachers proved to be very important in his life. Babur, as a man of perfect faith, was learned to know that the factors that ensure his victory in battles were first the judgment and destiny of the Almighty, and then in his own efforts and determination. Bobour has studied the absence of internal strife, confusion, and strict discipline as the vices that condemn defeat, and the most basic vices as freedom of the self, its enslavement, is the aspect of man’s defeat, both outwardly and inwardly. Keywords: Zahiriddin Muhammad Babur, "Boburnoma", social, political life, public administration, faith, ideological views, Naqshbandi sect, representatives of the sect, character, compassion, forgiveness, generosity, courage, victory, spiritual victory, the issue of pir and murid.